A National Comparison of Operative Outcomes of New and Experienced Surgeons. Issue 2 (February 2021) - Kelz, Rachel R.; Sellers, Morgan M.; Niknam, Bijan A.; Sharpe, James E.; Rosenbaum, Paul R.; Hill, Alexander S.; Zhou, Hong; Hochman, Lauren L.; Bilimoria, Karl Y.; Itani, Kamal; Romano, Patrick S.; Silber, Jeffrey H.
Abstract : Objective: To determine whether outcomes achieved by new surgeons are attributable to inexperience or to differences in the context in which care is delivered and patient complexity. Background: Although prior studies suggest that new surgeon outcomes are worse than those of experienced surgeons, factors that underlie these phenomena are poorly understood. Methods: A nationwide observational tapered matching study of outcomes of Medicare patients treated by new and experienced surgeons in 1221 US hospitals (2009–2013). The primary outcome studied is 30-day mortality. Secondary outcomes were examined. Results: In total, 694, 165 patients treated by 8503 experienced surgeons were matched to 68, 036 patients treated by 2119 new surgeons working in the same hospitals. New surgeons' patients were older (25.8% aged ≥85 vs 16.3%, P <0.0001) with more emergency admissions (53.9% vs 25.8%, P <0.0001) than experienced surgeons' patients. Patients of new surgeons had a significantly higher baseline 30-day mortality rate compared with patients of experienced surgeons (6.2% vs 4.5%, P <0.0001;OR 1.42 (1.33, 1.52)). The difference remained significant after matching the types of operations performed (6.2% vs 5.1%, P <0.0001; OR 1.24 (1.16, 1.32)) and after further matching on a combination of operation type and emergency admission status (6.2% vs 5.6%, P =0.0007; OR 1.12 (1.05, 1.19)). After matching on operation type, emergency admission status, and patient complexity, the difference between new and experienced surgeons' patients' 30-day mortality became indistinguishable (6.2% vs 5.9%, P =0.2391;OR 1.06 (0.97, 1.16)). Conclusions: Among Medicare beneficiaries, the majority of the differences in outcomes between new and experienced surgeons are related to the context in which care is delivered and patient complexity rather than new surgeon inexperience. Abstract : Supplemental Digital Content is available in the text